Kekuatan Hukum Akta Hibah Wasiat Berdasarkan Putusan MA Nomor 2979K/Pdt/2019 - Putri Zakia Yurahman; Busyra Azheri; Wetria Fauzi (Media of Law and Sharia, 2023)
A will or testament, according to Article 875 of the Civil Code, is a deed that contains information about a person's last message regarding what will happen to him when he dies. Cases related to testamentary grants in Supreme Court Decision Number 2979 K/Pdt/2019. In the case, it was explained that the will grant was given by a father to his son in a non-Chinese Buddhist family. This inheritance was from the couple Lay Tjin Ngo (plaintiff) and Sumita Chandra (late), and during Lay Tjin Ngo's marriage to Sumita Chandra, joint property had been obtained. The problem arose when Sumita Chandar, without the approval of Lay Tjin Ngo, made Testament Number 24 dated July 25, 2014, at Notary Kamelina, SH. The defendant's actions made Testament No. 24 dated July 25, 2014, even though there was no approval from The plaintiff, as the wife or partner of Sumita Chandra (late), is an act that violates and has caused losses to the plaintiff, who, as the wife of Sumita Chandra (late), is entitled to a portion of the joint assets of Sumita Chandra with the plaintiff. The problem discussed in this study is how the judge considers the deed of testamentary grants made by Sumita Chandra as the grantor to the defendant as the beneficiary of the will grant in terms of the perspective of joint assets and what the position of the will deed made by a notary is in terms of the perspective of shared assets. This research uses the case-based problem approach. The sources and types of data used are primary and secondary data. Based on the results of the research and discussion, it is stated that family law relates to joint property, and in the case of a testament made by a husband or wife when the spouse is still alive, the consent of the spouse is still valid.